2016
DOI: 10.3892/or.2016.5316
|View full text |Cite
|
Sign up to set email alerts
|

Testin is a tumor suppressor in non-small cell lung cancer

Abstract: Abstract. The Testin gene was previously identified in the fragile chromosomal region FRA7G at 7q31.2. It has been implicated in several types of cancers including prostate, ovarian, breast and gastric cancer. In the present study, we investigated the function of the candidate tumor-suppressor Testin gene in non-small cell lung cancer (NSCLC). In NSCLC cell lines, we observed lower expression of Testin compared to that noted in normal human bronchial epithelial cells. MTT assays, flow cytometry, clonogenic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Consistent with our findings, a previous study showed that overexpression of TES significantly inhibited breast cancer cell invasion and reduced breast cancer cell metastasis to the lung through blocking the secretion of matrix metallopeptidase-2 (MMP-2) [18]. Overexpression of TES also markedly inhibited the invasion and metastasis of endometrial carcinoma [19] and non-small cell lung cancer [21]. Thus, TES down-regulation may play important roles in the progression of different types of human cancers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, a previous study showed that overexpression of TES significantly inhibited breast cancer cell invasion and reduced breast cancer cell metastasis to the lung through blocking the secretion of matrix metallopeptidase-2 (MMP-2) [18]. Overexpression of TES also markedly inhibited the invasion and metastasis of endometrial carcinoma [19] and non-small cell lung cancer [21]. Thus, TES down-regulation may play important roles in the progression of different types of human cancers.…”
Section: Discussionsupporting
confidence: 90%
“…TES has been identified as a TSG in many types of tumors, such as uterine cancer [7], ovarian carcinoma [17], breast cancer [18], endometrial carcinoma [19], head and neck squamous cell carcinoma [20], and non-small cell lung cancer [21]. In the present study, we investigated the effect of TES on the viability of GC cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they presented inhibitory effect of TES on NSCLC cell xenograft formation and growth in vivo on athymic nude mice. These data suggest important role of testin in development and progression of NSCLC [48].…”
Section: Introductionmentioning
confidence: 99%
“…Testin participate in the processes of tumor growth, angiogenesis, and metastasis [10]. Many researchers stated involvement of testin in tumor progression, what suggest its potential usage in immunotherapy [7, 11]. Understanding the molecular functions of testin may be crucial in development personalized treatment.…”
mentioning
confidence: 99%
“…In humans, the TES gene is located in the FRG7G region on chromosome 7q31.2, which is believed to contain a tumour suppressor gene because of its lack of heterozygosity in multiple malignancies . The interest in TES mainly arises from the fact that it has been shown to be downregulated in an increasing number of human tumour types, in which its downregulation correlates with disease progression …”
Section: Introductionmentioning
confidence: 99%